Association of remnant cholesterol and lipid parameters with new-onset carotid plaque in Chinese population - Liu, Bo; Fan, Fangfang; Zheng, Bo; Yang, Ying; Jia, Jia; Sun, Pengfei; Jiang, Yimeng; Li, Kaiyin; Liu, Jiahui; Chen, Chuyun; Li, Jianping; Zhang, Yan; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Remnant lipoprotein cholesterol (RC) is an independent risk factor for cardiovascular disease (CVD). However, the relationships of remnant cholesterol and other conventional lipid parameters with new-onset carotid plaque are not fully understood in the Chinese community-based population. Materials and methods A total of 872 plaque-free participants (51.39 ± 4.96 years old) with no history of CVD were included in this study. The plasma concentrations of RC were calculated by subtracting low-density lipoprotein cholesterol (LDL-C) and high-density lipoprotein cholesterol (HDL-C) from total cholesterol (TC). Multivariate regression models were used to evaluate and compare the associations between RC and other lipid parameters and new-onset carotid plaque. Results After a mean 6.77-year follow-up, the incidence of new-onset carotid plaque was 188 (21.56%). RC was significantly associated with new-onset carotid plaque [Odd ratio (OR) = 1.57 per 1 mmol/L increase, 95% confidence interval (CI): 1.03–2.41, p = 0.038]. The highest tertile of RC (T3 group) had the highest risk of new-onset carotid plaque (OR = 2.53, 95% CI: 1.63–3.95). Similar results were seen for increased other lipid parameters, but decreased HDL-C levels. When adding another lipid parameter into the adjusted model with RC simultaneously, only RC remained significantly associated with new-onset carotid plaque after adjusting for other lipid parameters (all p value < 0.005). Furthermore, RC was strongly associated with new-onset carotid plaque in participants with lower baseline LDL-C levels. Conclusion Increased RC levels were superior to other conventional lipid parameters to be associated with new-onset carotid plaque in the Chinese community-based population. Furthermore, RC should be considered in participants with lower LDL-C levels for the purpose of early atherosclerosis prevention.